P105 Burkholderia latens—a new infection in CF patients. (16th November 2010) - Horsley, A; Perry, C; Martin, K; Webb, K; Kenna, D; Jones, A
Abstract : Background: Burkholderia latens was first recognised as a novel species of the Burkholderia cepacia complex (Bcc) in 2008. To date, there are no reports of pulmonary infection. Here, we report a cluster of three CF patients all with chronic infection by B latens, and all geographically linked. Patient details: Three patients have been identified as chronically infected with B latens : a 23-year female (FEV1 23% predicted), a 23-year M (FEV1 55%), and a 26-year female (FEV1 37%). The first two live within 1 mile of each other, and had been known to be infected with Bcc since childhood, though the organism was only finally identified as B latens in 2009. The third patient has been infected since May 2008, but had lived in the same town as the other patients until 2 years previously, and had attended the same paediatric centre. Microbiology: All B latens isolates were confirmed by recA sequencing at the national reference laboratory (Colindale), and PFGE profiles showed >90% similarity. Multiple isolates have been obtained from each of the three patients, and they are all considered chronically infected. Formal eradication has not been attempted. Clinical impact: Over the preceding 3 years, annual decline in FEV1 was 6.5% and 4.5% for the first two patients, though this deterioration was not attributed to Bcc. Annual decline in FEV1 for patient 3 was 1.5%, with no significant change in spirometry, rate of decline in spirometry or weight following isolation of B latens . There have been no cases of cepacia syndrome sepsis secondary to B latens . Summary: This is the first report of chronic pulmonary infection by B latens . All three subjects are geographically linked to the same town. The organism may come from a common environmental source, but cross infection cannot be ruled out. In this small sample there do not appear to have been any short-term unexpected adverse effects on lung health (patient 3), but it is not yet possible to infer the longer term effects of chronic B latens infection.